Pengaruh Mata Kuliah Kewirausahaan dan Lingkungan Kampus terhadap Minat Berwirausaha Mahasiswa Pendidikan Ekonomi UHKBPNP: Penelitian - Evran Saragih; Anton Luvi Siahaan; Eduward Situmorang (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of entrepreneurship courses and the This study aims to analyze the influence of entrepreneurship courses and campus environment on the entrepreneurial interest of students of Economic Education UHKBPNP. The population in this study were all students of Economic Education UHKBPNP totaling 90 students. The sampling technique was carried out using saturated sampling technique with a sample size of 90 students. The results of the normality test showed that the data were normally distributed with a significance value of 0.200 > 0.05. The multicollinearity test showed no symptoms of multicollinearity because the Tolerance value was > 0.10 and VIF < 10. The heteroscedasticity test showed no specific pattern because the distribution of points was random. The results of the t-test showed that there was a significant influence of entrepreneurship courses on students' entrepreneurial interest with (t count = 3.812 > t table = 1.987) and there was a significant influence of the campus environment on students' entrepreneurial interest with (t count = 7.396 > t table = 1.987). The results of the F test show that both variables simultaneously have a significant effect on students' entrepreneurial interest (f count = 47.775 > f table = 3.10). The coefficient of determination (R²) value of 0.523 indicates that 52.3% of the variation in students' entrepreneurial interest is influenced by entrepreneurship courses and the campus environment, while 57.7% is influenced by other factors not examined in this study.